TM Plasmons in a Cylindrical Superlattices (Lans) Wave-Guide Structure - H.M. Mousa; M.M. Shabat (Журнал нано- та електронної фізики)
In this work, we have investigated theoretically the propagation characteristics of TM plasmons in a cylindrical wave-guide structure of a lateral antiferromagnetic - non magnetic superlattices (LANS) bounded by a metal. We derived the Eigenmodes equation and study the dispersion properties of transverse magnetic (TM) plasmons which propagate on the waveguide. We found that, backward TM plasmons can be tuned by adjusting the thickness of the waveguide to small reduced radius. We also found that the plasmons turn from backward to forward when the bounded material is vacuum. We also illustrated the dependence of the wave index nx on the magnetic fraction f1 of (LANS). Larger propagation lengths of TM plasmons are realized at small reduced radius and less magnetic material in LANS. The energy flow on the waveguide is also analyzed. We studied the dependence of the power flow on the electric permittivity of the metal εm. More forward plasmons are observed by increasing εm.